Analisis Kapasitas dan Pemberdayaan Masyarakat di Desa Wisata Bagot, Samosir - Bernadet Sihombing; John Suprihanto (JURNAL DESTINASI PARIWISATA, 2022)
New tourist villages generally face general problems such as a lack of understanding about tourism and communityempowerment, so the community's lack of ability to cultivate the potential of the region. By equipping themselves withthe CCB concept of good management can maximize the performance of tourist villages. The problems that ariserelated to the capacity faced by the Bagot Tourism Village. The purpose of this study is to identify the capacity ofindividuals, organizations, and communities in the Bagot Tourism Village and to evaluate the capacity for communityempowerment in the Bagot Tourism Village. A qualitative approach was used in this study by conducting in-depthinterviews with informants who benefited directly and indirectly from the Bagot Tourism Village. The results of theanalysis that has been carried out that it was found that the Bagot Tourism Village at the individual, organizationaland community level has a moderate capacity. The evaluation carried out on the empowerment and capacity of theBagot Tourism Village shows that the social empowerment and psychological empowerment of the Bagot TourismVillage community are in the high category and political empowerment which is felt to be in the medium category.Keywords : Community capacity; Empowerment; Tourism village